Методи діагностики ятрогенних дисфоній у хірургії щитоподібної залози - Паламарчук, В. О.; Івановський, Р. Г. (Clinical Endocrinology and Endocrine Surgery, 2010)
Modern approaches in diagnostics of secondary voice disorders after thyroid surgery are shown. Efficiency of multivariate analysis of the functional state of larynx is analysed in a postoperative period. 679 patients were observed. Among them 462 patients (68%) had subjective complaints on voice disorders in early postoperative period. Spectral analysis of voice fixed disorders for 58 patients (8,6%), undirect laryngoscopy finds out violation of mobility of elements of larynx for 48 (7%) patients, sonography of larynx — in 51 (7,5%), direct endovideolaringoscopy — in 31 (4,5%). 26 (3,9%) patients had all subjective and objective signs of neuromuscle violations of larynx described above Thus most informative from the presented methods is a direct endovideolaryngoscopy in combination with the spectral voice analysis.